Line shape of the coherent population trapping resonance in the case of a Gaussian spatial profile of a light beam. (February 2022) - Yudin, V I; Basalaev, M Yu; Kovalenko, D V; Taichenachev, A V; Pollock, J; Hansen, A.; McGehee, W; Kitching, J
Abstract: For coherent population trapping (CPT) resonance excited by a bichromatic field in a closed Λ-system, we have obtained an analytical expression for the line shape in the case of a Gaussian profile of the radiation intensity distribution, taking into account the light shift of the reference transition frequency. Due to the spatial inhomogeneity of the light shift, the line shape is asymmetric. The dependence of the shift of the resonance peak position on the light intenisty is investigated.